Functional reconstruction of a hand that was severely deformed due to Jaccoud's arthropathy. (3rd April 2021) - Funamura, Kei; Ishikawa, Hajime; Kakutani, Rika; Abe, Asami; Otani, Hiroshi; Nakazono, Kiyoshi; Murasawa, Akira
Abstract: A 54-year-old woman suspected of having localised systemic sclerosis (SSc) started steroid treatment around 40 years old. She had Jaccoud's arthropathy in her right hand with severe deformities but no bone erosion. The metacarpophalangeal (MP) joint of the index through the little fingers was dislocated palmo-ulnarly with flexion contracture of about 120° and a swan-neck deformity. The palmar skin crease was digging deeply into the skin and was soggy. Severe boutonnière deformity of the thumb was also noted. Due to her severely deformed hand, she could not grasp large objects or show her hand in public. Reconstructive surgery was performed in two stages using finger joint arthroplasty or fusion at the digital joints. After surgery, the appearance as well as the function of the hand was successfully restored. She was able to grasp the steering wheel of her car and was extremely satisfied with the results of the surgery.